2015
DOI: 10.1039/c5ra03448e
|View full text |Cite
|
Sign up to set email alerts
|

Submicron ZnO raspberries as effective catalysts for Fries rearrangement

Abstract: o-Xylene-in-water emulsion droplets have been exploited as soft templates for the synthesis of submicrometer-sized raspberry-like ZnO morphologies. The optical properties, structure and morphology of the microstructures have been characterised by absorption and fluorescence spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction and selected area electron diffraction analysis. It has been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Other by-products including phenyl salicylate, xanthone, and phenyl 4-hydroxybenzoate were also found in the qualitative analysis. Taking into account the similar molecular structures between by-products and DPC [ 31 , 32 ] and the Fries rearrangement reaction mechanism [ 33 35 ], the mechanism of generation of the three by-products was preliminarily deduced. DPC has a phenolic ester structure.…”
Section: Resultsmentioning
confidence: 99%
“…Other by-products including phenyl salicylate, xanthone, and phenyl 4-hydroxybenzoate were also found in the qualitative analysis. Taking into account the similar molecular structures between by-products and DPC [ 31 , 32 ] and the Fries rearrangement reaction mechanism [ 33 35 ], the mechanism of generation of the three by-products was preliminarily deduced. DPC has a phenolic ester structure.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that the these hollow and template-free microstructures can act as greener catalysts for the Fries rearrangement of phenolic esters to p-hydroxyaryl carbonyl compounds with high turnover frequency. 76 In addition, the possibility of tuning the band gap with particle size has been advantageous for the photocatalytic decompositions of volatile organic compounds. 20 The unique advantages, including high environmental and electrical stabilities, high photoelectrical performance, and cost-effectiveness, have inspired the application of ZnO as typical photocatalysts toward industrial applications.…”
Section: Crystallinity and Applicationsmentioning
confidence: 99%
“…The morphology of the nanostructures, the crystalline orientation, and the presence of oxygen defects influence the photocatalytic activities and the chemical stability under the reaction conditions. , We have adopted a soft-templated strategy using o -xylene-in-water emulsion droplets for the synthesis of raspberry-like ZnO assemblies with sizes in the submicrometer regime. It has been observed that the these hollow and template-free microstructures can act as greener catalysts for the Fries rearrangement of phenolic esters to p -hydroxyaryl carbonyl compounds with high turnover frequency . In addition, the possibility of tuning the band gap with particle size has been advantageous for the photocatalytic decompositions of volatile organic compounds .…”
Section: Crystallinity and Applicationsmentioning
confidence: 99%